Terminology concepts and structural features of technique of walking with sticks - Shepelenko G.P; Prusik Krzysztof; Prusik Katarzyna; Iermakov S.S (Kharkov National Pedagogical University, 2012)
The purpose of work is an analysis of technique of walking with sticks. The views of specialists are shown to the problem of health of a man and influencing of walking with sticks on his level. Biomechanics phases of implementation of technique of walking are certain and described. Terminology concepts and forces which operate at walking with sticks are exposed. The analysis of general parameters which characterize walking is resulted. The most meaningful groups of muscles which accept active voice at walking are considered. The most essential directions of walking are exposed. Intercommunications of motions are certain at walking. The biomechanics criteria of motions are selected. It is marked that the general influencing of walking with sticks on the organism of man is related to the improvement of the functional state of the central nervous system, indemnifications of power inputs, by functional changes in the system of circulation of blood and decline of disease. Possibilities of application of walking with sticks are shown as a physical loading for the people of different age groups. Resulted recommendation on the technique of walking with sticks and its influencing on a health of man.